2021
DOI: 10.1021/acs.iecr.1c02891
|View full text |Cite
|
Sign up to set email alerts
|

Process Designs for Separating R-410A, R-404A, and R-407C Using Extractive Distillation and Ionic Liquid Entrainers

Abstract: Hydrofluorocarbon refrigerants are being phased out over the next two decades due to their high global warming potential. To separate and recycle refrigerants that form azeotropic mixtures, current distillation methods are inadequate and a new technology is required. Extractive distillation using an ionic liquid as the entrainer offers a solution. Vapor liquid equilibria data for refrigerants difluoromethane (HFC-32), chlorodifluoromethane (HCFC-22), pentafluoroethane (HFC-125), 1,1,1-trifluoroethane (HFC-143a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 73 publications
(123 reference statements)
1
51
0
Order By: Relevance
“…[45][46][47][48] Since the feasibility of using ILs in extractive distillation schemes 10,11 was shown in the early 2000s, many studies have evaluated their properties in mixtures with fluorinated refrigerants [13][14][15][16][17][18][19][20][21][22][23] and examined their use in HFC separations. 12,24 ILs have also been the subject of computer-aided molecular design research, which has aimed to take advantage of their tunability to simultaneously design IL entrainers and optimize the separation processes in which they are used. 49,50 Regression of thermodynamic models Because equations of state (EoS) are continuous and differentiable functions, they are wellsuited for computer-aided process design and optimization.…”
Section: Ionic Liquids As Entrainersmentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47][48] Since the feasibility of using ILs in extractive distillation schemes 10,11 was shown in the early 2000s, many studies have evaluated their properties in mixtures with fluorinated refrigerants [13][14][15][16][17][18][19][20][21][22][23] and examined their use in HFC separations. 12,24 ILs have also been the subject of computer-aided molecular design research, which has aimed to take advantage of their tunability to simultaneously design IL entrainers and optimize the separation processes in which they are used. 49,50 Regression of thermodynamic models Because equations of state (EoS) are continuous and differentiable functions, they are wellsuited for computer-aided process design and optimization.…”
Section: Ionic Liquids As Entrainersmentioning
confidence: 99%
“…11 More recent work has used data generated from these studies to regress thermodynamic models then perform process design, optimization, technoeconomic analyses, and life cycle assessments for IL-enabled HFC separation schemes. 12,[24][25][26] However, because millions of theoretical ILs are available, each with unique properties, trial-and-error molecular and process design is intractable since each HFC within a refrigerant blend exhibits a different boiling point and solubility with an IL. 27 This necessitates a framework which integrates experiments, mathematical models, and computational optimization to concurrently design ILs and separation processes for azeotropic HFC refrig-erant mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids were first introduced as entrainers in 2001 by the BASF Chemical Company and patented in 2004 by Wolfgang Arlt et al , Only two institutions, BASF and Eindhoven University of Technology (EUT), have published details regarding the experimental setup for testing extractive distillation with ILs. However, 33 articles have been published on the simulation of ILs as entrainers for extractive distillation. Table S3 provides a summary of all of the published material on extractive distillation with IL entrainers, including the (i) components being separated, (ii) IL entrainer, and (iii) thermodynamic model used to predict the equilibrium of the system. Most of these separations were binary systems; however, the italicized labels shown in Table S3 represent multicomponent mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, there is no known solubility data for HCFC-142b in ILs. In this work, the IL [C 4 C 1 im]­[PF 6 ] was selected for simulations because of the VLE data available for seven of the refrigerants and the higher selectivity than using [C 2 C 1 im]­[Tf 2 N], as discussed in our previous work …”
Section: Introductionmentioning
confidence: 99%
“…Shiflett et al investigated the selectivity differences for separating R-410A using several imidazolium-based ILs ([C 4 C 1 im]­[C 1 CO 2 ], [C 4 C 1 im]­[SCN], [C 6 C 1 im]­[Cl], [C 6 C 1 im]­[FAP], [C 4 C 1 im]­[BF 4 ], and [C 4 C 1 im]­[PF 6 ]). The results revealed that [C 6 C 1 im]­[Cl] and [C 4 C 1 im]­[C 1 CO 2 ] had the highest ideal selectivity for separating R-410A at 298.15 K. Based on their previous research, they continued to study the separation of four blends (R-410A, R-407C, R-404A, and R-410A/R-22) using two ILs ([C 2 C 1 im]­[Tf 2 N] and [C 4 C 1 im]­[PF 6 ]) . By comparing six ILs with two cations (imidazolium [C x C 1 im] + and phosphonium [P 6,6,6,14 ] + ) and halogen anions ([Cl] − , [Br] − , and [I] − ), Shiflett et al also pointed that [P 6,6,6,14 ]­[Cl] and [C 6 C 1 im]­[Cl] are potential entrainers for separating R-410A by extractive distillation.…”
Section: Introductionmentioning
confidence: 99%